Stellate ganglion intervention for chronic pain: A review - Qingyang Luo; Song Wen; Xinran Tan; Xi Yi; Song Cao (Ibrain, 2022)
Abstract Stellate ganglion (SG) intervention is currently widely being studied in many kinds of chronic pain. As one of the convenient ways to treat the sympathetic nervous system, the indications for stellate ganglion intervention (SGI) include complex regional pain syndrome, postherpetic neuralgia, cancer pain of different origins, orofacial pain, and so forth. SGI refers to the reversible or irreversible blocking of the cervical sympathetic trunk, cervical sympathetic ganglion, and their innervation range through noninvasive or minimally invasive treatment. Current treatment options include stellate ganglion block (SGB), SG pulsed radiofrequency, continuous radiofrequency treatment, and noninvasive SGB. In particular, SGB continues to be one of the most studied methods in chronic pain management. However, a single SGB usually provides only short‐term effects; repeated SGB may result in complications such as hoarseness, light‐headedness, and vessel or nerve injury. Meanwhile, the mechanism of SGI is still unclear. This review discusses the research progress of SGI methods, effectiveness, complications, and possible mechanisms in the management of chronic pain.